Prediction of endotracheal tube size in pediatric patients: Development and validation of machine learning models - Zhou, Miao; Xu, Wen.Y.; Xu, Sheng; Zang, Qing L.; Li, Qi; Tan, Li; Hu, Yong C.; Ma, Ning; Xia, Jian H.; Liu, Kun; Ye, Min; Pu, Fei Y.; et al. (Frontiers in Pediatrics, 2022)
Objective: We aimed to construct and validate machine learning models for endotracheal tube (ETT) size prediction in pediatric patients. Methods: Data of 990 pediatric patients underwent endotracheal intubation were retrospectively collected between November 2019 and October 2021, and separated into cuffed and uncuffed endotracheal tube subgroups. Six machine learning algorithms, including support vector regression (SVR), logistic regression (LR), random forest (RF), gradient boosting tree (GBR), decision tree (DTR) and extreme gradient boosting tree (XGBR), were selected to construct and validate models using ten-fold cross validation in training set. The optimal models were selected, and the performance were compared with traditional predictive formulas and clinicians. Furthermore, additional data of 71 pediatric patients were collected to perform external validation. Results: he optimal 7 uncuffed and 5 cuffed variables were screened out by feature selecting. The RF models had the best performance with minimizing prediction error for both uncuffed ETT size (MAE = 0.275 mm and RMSE = 0.349 mm) and cuffed ETT size (MAE = 0.243 mm and RMSE = 0.310 mm). The RF models were also superior in predicting power than formulas in both uncuffed and cuffed ETT size prediction. In addition, the RF models performed slightly better than senior clinicians, while they significantly outperformed junior clinicians. Based on SVR models, we proposed 3 novel linear formulas for uncuffed and cuffed ETT size respectively. Conclusion: We have developed machine learning models with excellent performance in predicting optimal ETT size in both cuff and uncuffed endotracheal intubation in pediatric patients, which provides powerful decision support for clinicians to select proper ETT size. Novel formulas proposed based on machine learning models also have relatively better predictive performance. These models and formulas can serve as important clinical references for clinicians, especially for performers with rare experience or in remote areas.